Preferences Activism of Islamic Spiritual (Rohis) in Schools and Madrasas in Yogyakarta: From Narrative Islamism to Popular Culture - Rohinah, Rohinah (Jurnal Pendidikan Islam, 2022)
Purpose – The existence of Rohis in schools and madrasas is often imaged as a movement for Islamization and school da’wah. However, globalization and modernization inevitably bring new directions for the next Rohis movement and is evident in its various activism. This study aims to determine the preferences of Rohis activism in schools and madrasas that have experienced a shift from Islamism “right” towards popular culture. Design/methods/approach – This research method is a qualitative case study. The subjects of this research are Rohis activists in MAN 1 Yogyakarta and SMAN 5 Yogyakarta. This study collects data through in-depth interviews, participant observation, and documentation. Data analysis uses the Miles and Huberman model with interactive analysis through data reduction, data presentation, and conclusions. Findings – The results of this study indicate that the Rohis’ activism preferences appear in the spaces they create as a form of negotiation between obedience and modernity, including manifesting in the form of religious events, the theme of the study, and the name of the program/division. Research implications/limitations – The implications of this research in the world of education provide insight and views that modernization and globalization cannot be avoided, especially for Muslim youth who are members of Rohis. Practical implications – This research shows that school policies are more progressive and responsive to changing times.